Validation of DPOAE screening conducted by village health workers in a rural community with real-time click evoked tele-auditory brainstem response. - Ramkumar, Vidya; Vanaja, C. S.; Hall, James W.; Selvakumar, K.; Nagarajan, Roopa (International Journal of Audiology, 2018)
Objective: This study assessed the validity of DPOAE screening conducted by village health workers (VHWs) in a rural community. Real-time click evoked tele-auditory brainstem response (tele-ABR) was used as the gold standard to establish validity. Design: A cross-sectional design was utilised to compare the results of screening by VHWs to those obtained via tele-ABR. Study samples: One hundred and nineteen subjects (0 to 5 years) were selected randomly from a sample of 2880 infants and young children who received DPOAE screening by VHWs. Method: Real time tele-ABR was conducted by using satellite or broadband internet connectivity at the village. An audiologist located at the tertiary care hospital conducted tele-ABR testing through a remote computing paradigm. Tele-ABR was recorded using standard recording parameters recommended for infants and young children. Wave morphology, repeatability and peak latency data were used for ABR analysis. Results: Tele-ABR and DPOAE findings were compared for 197 ears. The sensitivity of DPOAE screening conducted by the VHW was 75%, and specificity was 91%. The negative and positive predictive values were 98.8% and 27.2%, respectively. Conclusions: The validity of DPOAE screening conducted by trained VHW was acceptable. This study supports the engagement of grass-root workers in community-based hearing health care provision.